Da representação social do ser professor da EJA à descoberta de seu aluno como referente - Albino, Giovana Gomes (2010)
Evidence of learning object like representation to social teachings that active in the education of young and adult with the point of view of the ―To be teacher‖ in this modality of teaching, to direct the intention, this research is way, understand the existence of this representation in center acting teachers in the initial periods of the EJA in the Rio Grande do Norte and its reasoning the theories of social representation (MOSCOVICI, 1978, 2003; JODELET, 2001; ABRIC, 1998). We interviewed one hundred and ten (110) teachers who work at schools in the Metropolitan Regions of Natal. We use two procedures: focal group (GATTI, 2005) and multiple classification analysis MCA (ROAZZI, 1995).Thus us with the focal group, attended by eight (08) teachers and seek to know understanding their ideas about EJA, what was possible from the content analysis (BARDIN, 1977; FRANCO, 2007) of the following category: the teacher s view of the EJA context. Developing the MCA, we met twenty (20) teachers in the first stage, free-word association technique FAT (ABRIC, 1998), and ninety in the second stage, including the participants of the focal group. The results of this procedure were submitted to multidimensional analysis and content analysis. The first showed three facets: having and being teacher dimension (ideal), which was about the example teacher s characteristics and behaviors; teacher/ student relation which was about the difficulties and doubts of this relationship as well as its success; at last, conflicting dimension from/ with practice, based on the conflicts experienced by the teachers as EJA workers. Content analysis based on the theme organization from the interpreted data showed four categories: resources to be a teacher which also brought out the definition of an ideal teacher; talk about teaching which disclosed teachers thoughts about the knowledge and being a teacher; obstacles to EJA which showed situations and conditions that prejudice EJA development; and also admission as EJA teacher: viewing reasons which revealed the reasons why teachers went to EJA even though they were formed to deal with children. The conjoint analysis us evidenced the little the dominion of the teachers a participation these search at respect of origin, of the meaning of the character while the singular of EJA modality of teaching the conformation of the social representation from the ―To be‖ on the general vision dissociating with it of inexistence of a social representation of ―to be teacher of the EJA‖ white striking element in the reference at singularity that define the related modality of teaching